"(In)justice" of suffering in family law - Đerlek Minela (Trendovi u Poslovanju, 2023)
The idea of justice is often denied in family relationships due to their emotional nature. The term emotional nature together with the term "justice" implies that emotionality makes concepts impossible and that family relationships as such are quite inaccessible from the aspect of justice. In this sense, the problem arises in the situations of modern society, where through marriage as a "community of a man and a woman" the entire context of the family is established as an institution of success, harmony and getting along, so children are excluded from participating in the realization of this community. Contemporary understandings of divorce have disrupted responsibility in relation to the family, the idea of "guilt" becomes a relic, and the need to justify a wrong choice is neglected. However, when the termination of marriage or extramarital union occurs in the phase of partner relations, the emotional reaction of adults is different. The problem arises when the end of joint life occurs between the parents, where the disintegration of the only "refuge and source of love" creates a feeling of deprivation, injustice and painful feeling.